Clinical outcomes and management of tibial plateau fractures in Ethiopia: A prospective cohort study - Adugnaw Bogale Worku; Molla Asnake Kebede; Alemayehu Dagne Abate; Solyana Haileselassie Admassie; Meskerem Girma; Bekalu Wubshet Zewde; Mekuanint Dessie; Hashime Meketa Negatie; Adefris Getachew Techane; Abebe Agegn Wudineh (PLoS ONE, 2025)
Background Tibial plateau fractures, accounting for approximately 1% of adult fractures, are often associated with significant long-term complications such as pain, stiffness, and posttraumatic arthrosis. The optimal treatment approach remains controversial, particularly in resource-limited settings. This study investigated the factors influencing the clinical outcomes of patients with tibial plateau fractures in Ethiopia. Objective Tibial plateau fractures, though common in trauma cases, have been poorly studied in sub-Saharan Africa, particularly in Ethiopia. The primary purpose of this study was to examine the factors influencing the clinical outcomes of patients with tibial plateau fractures and to assess the efficacy of conservative treatment versus surgical intervention. This research aims to provide insights into managing tibial plateau fractures in resource-limited settings, with the hope of contributing to improved clinical practices. Methods A total of 191 patients with tibial plateau fractures were recruited from Tibebe Ghion Referral Hospital and Felegehiwot Specialized Hospital between February 1, 2018, and February 2022. Demographic, clinical, and radiological data were analyzed, and treatment outcomes were assessed via Rasmussen’s knee functional outcome score. A correlation analysis was performed to identify factors impacting functional outcomes. Logistic regression was used to identify factors influencing clinical outcomes. Results The study population was predominantly male (73.8%), with a mean age of 45 years. Road traffic accidents (41.9%) were the most common cause of injury. Schatzker type I fractures (27.2%) were the most common, and compound fractures accounted for 21% of the fractures. The average time to definitive management was 1.59 weeks, with 35% of patients undergoing open reduction and internal fixation (ORIF). The duration of immobilization and weight-bearing significantly influenced functional outcomes. Patients who were immobilized for less than 4 weeks had better outcomes, with functional scores 54 times better than those of patients who were immobilized for more than 8 weeks (p < 0.01). Early initiation of partial weight-bearing also improved outcomes. A strong negative relationship was found between the duration of immobilization and functional outcomes (r = -0.705, p < 0.01). Conclusion This study highlights the importance of early mobilization and optimal management of tibial plateau fractures for improving functional outcomes. Timely treatment, especially regarding immobilization and weight-bearing, is crucial for achieving better results. These findings emphasize the need for more standardized treatment protocols and further research on tibial plateau fractures in sub-Saharan Africa to increase patient care in resource-limited settings.